Factors that affect a better fiscally autonomous government: Evidence from an Indonesian newly autonomous region - Sukmadilaga, Citra; Pramanda, Muhamad Andri Arif; Yadiati, Winwin; Yunita, Devianti (Edelweiss Applied Science and Technology, 2024)
This study aims to investigate the influence of fiscal decentralization and socio-economic determinants on fiscal autonomy, taking into account anti-corruption efforts as a moderating variable. This study uses a dataset that spans 5 years and focuses specifically on 74 recently established autonomous regions in Indonesia after the year 2004. This study shows that the factors that indicate fiscal decentralization, such as locally created sources of funds and means of profit sharing, have a favorable and significant influence on fiscal autonomy. In contrast, total allocated funds have a detrimental and significant impact, but the special fund has a negligible impact on fiscal autonomy. This study shows a strong and statistically significant correlation between local investment and fiscal autonomy when socio-economic aspects are taken into account. However, the analysis showed that inward investment has an unfavorable impact that is not statistically significant. Furthermore, this study shows that anti-corruption, when treated as a separate factor, has a favorable and notable influence. Furthermore, when used as a moderating variable, it can serve as a quasi-moderator for the relationship between each of the independent variables and fiscal autonomy, which acts as the dependent variable. His study contributes to the existing body of knowledge on fiscal decentralization by providing a more comprehensive understanding of its influence on fiscal autonomy.